EFEKTIFITAS MODEL PBL DALAM MENINGKATKAN KEMAMPUAN MATEMATIKA MAHASISWABERBANTUAN BUKU AJAR MATAKULIAH ANALISA VEKTOR - Mushlihuddin, Rahmat; Nurafifah, Nurafifah (Universitas PGRI Sumatera Barat, 2018)
The low student learning outcomes suggest that lessons learned in the classroom are ineffective. Effective learning is a learning that affects the characteristics of student learning such as students' math skills. To help researchers in solving the problem then the researcher will use a textbook, hopefully, after this research, the researcher can develop textbook which applied in this research. The purpose of this study is to 1) Does the PBL model can improve students' math skills in vector analysis courses in FKIP UMSU? 2) Is the PBL model effective in improving students' math skills in vector analysis courses at FKIP UMSU ?. This research is a quasi-experiment research. The data analysis technique is done from the test stages of data description, then the prerequisite test is the normality test and hypothesis test. The results of this study are 1) PBL model can improve reasoning and proofing ability, and solving student math problems in vector analysis course 2) PBL model effective in improving students' math skills in vector analysis courses